Pengaruh Inovasi Guru terhadap Keaktifan Belajar Peserta Didik pada Mata Pelajaran IPS SMP Negri 213 Jakarta (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
The purpose of this study is to examine the extent of the influence of teacher innovation on the learning activeness of seventh-grade students in Social Studies (IPS) at SMPN 213 Jakarta. This research employs a quantitative approach with an ex post facto design. The sample consisted of 165 students selected using a simple random sampling technique. Data were collected through a questionnaire based on a Likert scale. The results of the data analysis indicate a positive and significant relationship between teacher innovation and students' learning activeness, as evidenced by a significance value of 0.000 (< 0.05). Furthermore, teacher innovation contributes 40.3% to students' learning activeness, while the remaining 59.7% is influenced by other factors not examined in this study. These findings emphasize the crucial role of innovative teachers in creating interactive learning environments and enhancing students’ active participation in the learning process.